Modern Techniques for Nano- and Microreactors/-reactions - Caruso, Frank; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
-Encapsulation by Miniemulsion Polymerization By K. Landfester and C. K. Weiss -Enzyme-Encapsulated Layer-by-Layer Assemblies: Current Status and Challenges Toward Ultimate Nanodevices By K. Ariga, Q. Ji, and J. P. Hill -Non-LBL Assembly and Encapsulation Uses 1 of Nanoparticle-Shelled Hollow Spheres 2 By G.C. Kini, S. L. Biswal, and M. S. Wong -Polymersomes: A Synthetic Biological Approach to Encapsulation and Delivery By M. Massignani, H. Lomas, and G. Battaglia -Reaction Vessels Assembled by the Sequential Adsorption of Polymers By A.D. Price, A.P.R. Johnston, G.K. Such, and F. Caruso
Encapsulation by Miniemulsion Polymerization -- Enzyme-Encapsulated Layer-by-Layer Assemblies: Current Status and Challenges Toward Ultimate Nanodevices -- Non-Layer-by-Layer Assembly and Encapsulation Uses of Nanoparticle-Shelled Hollow Spheres -- Polymersomes: A Synthetic Biological Approach to Encapsulation and Delivery -- Reaction Vessels Assembled by the Sequential Adsorption of Polymers.
Keywords: Chemistry; Polymers; Biochemistry; Pharmacy; Chemistry; Polymer Sciences; Medicinal Chemistry; Pharmacy; Biochemistry, general; Electrochemistry